2022
DOI: 10.1088/1361-6463/aca6f7
|View full text |Cite
|
Sign up to set email alerts
|

Surface recombination velocities for the (100) and (001) crystal faces of bismuth vanadate single crystals

Abstract: Bismuth vanadate (BiVO4) is widely used as a photocatalyst for water splitting, and its carrier lifetime is the most essential parameter for photocatalysts. In this study, we characterized the carrier lifetime in BiVO4 single crystals on the (100) and (001) crystal faces using the microwave photoconductivity decay (μ-PCD) method. For the (001) face, the observed μ-PCD curves with excitation by a 266 nm laser had no injected photon density dependence. In contrast, those excited using a 355 nm laser had an injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, the μ-PCD curves of the unpolished face show slight injected photon density dependence, while those of the polished face show no injected photon density dependence. This indicates that the carrier recombination of the unpolished face is dominated by the Shockley-Read-Hall (SRH) recombination, 63 while that of the polished face is dominated by the sufficiently fast recombination at the bulk recombination center which is similar to SrTiO 3 . 60,62 In addition, the Auger and bimolecular recombination which strongly depend on charge carrier concentration are negligible.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the μ-PCD curves of the unpolished face show slight injected photon density dependence, while those of the polished face show no injected photon density dependence. This indicates that the carrier recombination of the unpolished face is dominated by the Shockley-Read-Hall (SRH) recombination, 63 while that of the polished face is dominated by the sufficiently fast recombination at the bulk recombination center which is similar to SrTiO 3 . 60,62 In addition, the Auger and bimolecular recombination which strongly depend on charge carrier concentration are negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Yttrium aluminum garnet (YAG) lasers with wavelengths of 266 and 355 nm and pulse width of 1 ns were used as excitation light sources (FTSS 266-200 and FTSS 355-50, CryLas). 58,60,61,63,65 The spot size 63 of the two lasers was 0.13 cm -2 . The laser intensity was 0.06-0.6 mW for the 266 nm laser and 0.2-4.0 mW for the 355 nm laser.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it can also be concluded that defects directly dominate carrier recombination, which affects the material performance. Several measurements have been performed to observe the carrier recombination process [22,23]. Among these techniques, microwave photoconductivity decay (µ-PCD) and time-resolved photoluminescence (TR-PL) are the highly sensitive measurements used to observe the minority carrier recombination process when the charge carrier density is low [24].…”
Section: Introductionmentioning
confidence: 99%